2019
DOI: 10.2147/opth.s233273
|View full text |Cite
|
Sign up to set email alerts
|

<p>Baseline Predictive Factors of Visual Outcome and Persistence of Subretinal Fluid Based on Morphologic Changes in Spectral Domain Optical Coherence Tomography in Patients with Idiopathic Central Serous Chorioretinopathy</p>

Abstract: BackgroundTo determine the influence of spectral domain optical coherence tomography (OCT) changes on visual outcome and persistence of subretinal fluid (SRF) in patients with idiopathic central serous chorioretinopathy (CSCR).Materials and methodsIn a retrospective study done in 48 eyes of 45 patients diagnosed as CSCR, all eyes were subjected to fundus photography, spectral domain OCT, and fluorescein angiography (FA) in selected cases.ResultsRetinal pigment epithelium detachment was present in 22.91% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…These cut-off values are close to the 75 th percentiles of our study's predictive values: choroidal thickness of >450 µm and age of >45 years. In contrast to some reports, we did not observe any association between either baseline BCVA or CST and the disease episode length [24,25].…”
Section: Discussioncontrasting
confidence: 99%
“…These cut-off values are close to the 75 th percentiles of our study's predictive values: choroidal thickness of >450 µm and age of >45 years. In contrast to some reports, we did not observe any association between either baseline BCVA or CST and the disease episode length [24,25].…”
Section: Discussioncontrasting
confidence: 99%
“… 16 30 31 The overall incidence of HRDs in our study was 35.48%. This is relatively low compared with the incidence rate of 66%, 65%, 57.4% and 50% in the studies by Yalcinbayir et al , 16 Maruko et al , 29 Lai et al 18 and Suwal et al 32 , respectively. Lee et al 17 stated that increased number of HRDs was associated with recurrences.…”
Section: Discussionmentioning
confidence: 62%
“…However, they did not observe any correlation between number of HRDs and the final visual outcome. In their study, Suwal et al 32 found that eyes with HRDs had persistence of SRF at the end of 3 months and were associated with poor visual outcome.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Early morphologic changes on OCT can predict visual outcome and persistence of fluid. [20] If fluid persists, laser photocoagulation or photodynamic therapy may be considered. [21,22]…”
Section: Central Serous Chorioretinopathy (Cscr)mentioning
confidence: 99%